A new species of Mathania Oberthür, 1890 from Peru (Lepidoptera, Pieridae) - Farfán, Jackie; Lamas, Gerardo; Cerdeña, José (Zootaxa, 2020)
A new species of the genus Mathania Oberthür, 1890, M. hughesi Lamas, Farfán & Cerdeña, sp. n. is described from the southwestern slopes of the Andes of Peru, associated with xerophytic environments, between 2300 and 3500 m elevation. This new species is distinguishable from its congeners by the following external character: a black band on forewing dorsal surface at the end of the discal cell, extending from the costal margin to the base of cell M3-CuA1. Adults and male and female genitalia are illustrated and compared to other species of Mathania. In addition, we report Ligaria cuneifolia (R. et P.) Tiegh. (Loranthaceae) as host plant of M. hughesi.